Orleans: A Framework for Cloud Computing - Bykov, Sergey; Geller, Alan; Kliot, Gabriel; Larus, Jim; Pandya, Ravi; Thelin, Jorgen (Microsoft Research, 2010)
Client + cloud computing is a disruptive, new computing platform, combining diverse client devices – PCs, smartphones, sensors, and single-function and embedded devices – with the unlimited, on-demand computation and data storage offered by cloud computing services such as Amazon’s AWS or Microsoft’s Windows Azure. As with every advance in computing, programming is a fundamental challenge as client + cloud computing combines many difficult aspects of software development. Orleans is a software framework for building client + cloud applications. Orleans encourages use of simple concurrency patterns that are easy to understand and implement correctly, building on an actor-like model with declarative specification of persistence, replication, and consistency and using lightweight transactions to support the development of reliable and scalable client + cloud software.
Superseded by SOCC '12 publication. Please read and cite that publication.